2021
DOI: 10.1002/iub.2461
|View full text |Cite|
|
Sign up to set email alerts
|

T‐cell immunoglobulin and ITIM domain, as a potential immune checkpoint target for immunotherapy of colorectal cancer

Abstract: The importance of the tumor microenvironment in cancer progression has been well studied for many years. Immune checkpoint inhibitors (ICIs) are regarded as potential strategies in enhancing the immune responses in patients with cancer, particularly colorectal cancer (CRC). Notably, CRCs are extraordinarily heterogeneous and mostly are microsatellite‐stable (MSS) or cold tumors, which means that the immune response is not usually as strong as that of foreign cells. T‐cell immunoglobulin and ITIM domain (TIGIT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 136 publications
0
15
0
Order By: Relevance
“…Meanwhile, PIGR had a negative correlation with tumor-infiltrating NK cells and Tcm cells. Studies have demonstrated that immune checkpoint inhibitors have been regarded as potential strategies for enhancing immune responses in patients with CRC [ 42 ]. We found that the expression of PIGR had a positive relationship with several immune checkpoints, including IDO1, CD274, PDCD1, CTLA4, and LAG3.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PIGR had a negative correlation with tumor-infiltrating NK cells and Tcm cells. Studies have demonstrated that immune checkpoint inhibitors have been regarded as potential strategies for enhancing immune responses in patients with CRC [ 42 ]. We found that the expression of PIGR had a positive relationship with several immune checkpoints, including IDO1, CD274, PDCD1, CTLA4, and LAG3.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells, nonmalignant cells, immunocytes, tumor-associated macrophages (TAMs), cancer-associated fibroblasts (CAFs), myeloid-derived suppressor cells (MDSCs), natural killer (NK) cells, dendritic cells (DCs) and tumor-associated neutrophils (TANs) make up the tumor microenvironment (TME) ( 44 , 45 ). TIGIT was highly positively correlated with the ESTIMATE score in all of the cancers included, which indicated an advanced cancer stage with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These ligands primarily initiate the inhibitory signal through affecting the cytoplasmic domain and the immunoreceptor tyrosine-based inhibition motif (ITIM) after binding to TIGIT. 30 Fap2 protein has been found to be involved in the binding of F.n to cancer cells and can interact directly with TIGIT which is mainly expressed on NK, Treg, CD8 + and CD4 + T cells. 31 The binding of Fap2 to TIGIT can thereafter inhibit the activity of NK cells against tumor cells which can lead to the growth and progression of CRC.…”
Section: Mechanisms Through Which Fn Can Promote Crcmentioning
confidence: 99%